Daily field checking list by Walter Rosene, April 9, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Little Wall Lake and Boone County by Walter Rosene, Bob Walker, Mary Sturtz and George O. Hendrickson, April 9, 1939. Also notes there was no food in the Great Horned Owl nest. Plustek--flatbed